The Effect of Gypsum on the Performance of Intumescent Coating - Md Suhaimy, Ahmad Syafiq (Universiti Teknologi PETRONAS, 2009)
This study investigates the effect of gypsum to theperformance of intumescent coating. Intumescent or fire retardant coatings are one of the most efficient ways to protect materials against fire. In fact, it is generally known that acid source, carbon source, binding agent and blowing agent are the main ingredients of such a paint. Inthis project work, effect of using gypsum as additive in intumescent coating were investigated by performing fire test to sample coated with certain intumescent coating composition and by using Scanning Electron Microscope (SEM). All the results indicated that gypsum can increase fire retardation time which means intumescent coating modified with gypsum can withstand higher temperature and can last for longer time. This study and improvement of intumescent coating will help the constructions industry by producing better intumescent coating.